Harnessing Change from Within: Proprietary Case Studies as Tools for Inducing Diagnosis and Stimulating Action - Sweetman, Kate; Maital, Shlomo (Senate Hall Academic Publishing, 2006)
Case studies are widely used for educating managers. But they can also be a powerful tool for implementing change and for stimulating leadership and empowerment. This essay describes how the first author used case studies to drive a “choose to lead” program at Verizon, for large groups of managers. We show how to write proprietary (confidential) case studies for use in such programs and describe the five key principles for such studies. “Become who you are,” Nietzsche counseled. We show how internal case studies can help companies, and their managers, become who they truly are and hope to become.
Keywords: case studies; leadership; change management